A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF MADRASAH ALIYAH DAR EL HIKMAH PEKANBARU IN SELECTING CORRECT TROUBLESOME VERBS - - Pahmi; Novfelaningrum Edjuista (Politeknik Negeri Bengkalis, 2018)
Abstract: English mastery requires students to have sufficient knowledge about four skills, namely listening, speaking, writing and reading. In addition, other knowledge such as grammar is crucial too. Regarding grammar, students often get difficulty to use English accurately. This descriptive study aimed at finding out studentsâ€™ ability in selecting correct troublesome verbs. The study result showed that the level of studentsâ€™ ability was at mediocre level, 44.72. Furthermore, it showed that the highest score obtained by the students was 65, while the lowest score was 30. For the classification of troublesome verb, the most difficult was to differentiate the use of â€œbring and takeâ€ where 6 students (33.33%) were in very poor level.Keywords: Study, studentsâ€™ ability, troublesome verbs